ANALISIS BAURAN PEMASARAN TERHADAP KEPUTUSAN MEMILIH RUMAH (Studi Kasus di PT. Gading Anugerah Abadi di Malang) - Linda Ayu Susianti; Nunung Nurastuti Utami (Politeknik Negeri Malang, 2017)
This study aimed to analyze the influence of marketing mix variables the decision to choose a house. This type of research is explanatory research, the research approach used is quantitative. The sample in this study as many as 52 people. Mechanical analysis using multiple regression analysis, F test and t test. Based on the results of the analysis show that the marketing mix consisting of product, price, distribution channels, and simultaneous promotion significantly influence the decision to choose a house. Based on t test results showed that the product, price, distribution channels, and promotional partially significant effect on the decision to choose a house. Variable products the dominant influence on the decision to choose a house.